Population aging and the future of Canadian healthcare - Bezuko, Jane (My University, 2016)
The population of the world is aging, and the aging population should not be considered to be an insignificant contributor to increasing healthcare costs in Canada. This paper will explore the effects of aging on the healthcare system in Canada, and will address issues such as chronic illnesses associated with aging, fragmentation of healthcare services, use of an acute care model, and lack of specialized gerontological nursing education programs as contributing factors to why aging is a significant cost driver in healthcare. In addition, this paper will provide recommendations to transform Canada’s healthcare system in order to deliver sustainable and cost-effective healthcare for all.
Keywords: healthcare; aging; Canada